IMPLEMENTASI DAN ANALISIS METODE CASE BASED REASONING PADA DIAGNOSIS AWAL PENYAKIT SALURAN PERNAPASAN : Case Based Reasoning, Diagnosis, Expert System, Respiratory tracr. - Wahyuning Astuti, Reny; Puspitorini, Sukma; Pangestu, Prayogo (JURNAL AKADEMIKA, 2023)
Respiratory tract disease is a disease that can spread quickly in the community. Although mild, the disease is still dangerous for the very young and adults with limited cardiopulmonary function. This causes many local people to seek treatment at the Pondok Table Health Center, making doctors treat various types of diseases, especially influenza, ISPA, Faringitis and other respiratory diseases. However, in the current pandemic era, coupled with the Covid-19 Virus, it is enough for doctors to have to work extra to deal with various symptoms of the same respiratory disease. Therefore, it is necessary to apply an expert system for early diagnosis of respiratory tract disease by applying the Case Based Reasoning method. The Case-based reasoning method has the ability to provide more accurate diagnosis results, by comparing new cases and old cases using Similarty calculations, where this system will help patients to diagnose early disease, as well as provide disease information and treatment solutions. To make a diagnosis on this expert system application, input data is needed in the form of disease data, symptom data and case base data. And this application produces output data in the form of patient diagnosis reports.